2022
DOI: 10.1088/1361-6463/ac7115
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced charge separation at Zn-Pd/TiO2 hybrids interface for enhanced electrochemical and photocatalytic activity

Abstract: One dimensional nanostructures based hybrids have proven to be potent for photocatalytic applications. The hybrids having modified interface play a vigorous role in enrichment of photocatalytic activity by electronic interaction. Electronic interaction at interface occurs by the formation of electronic barriers (Ohmic/Schottky) that affects the transport of charge carriers and hence photocatalytic activity. The present work reports the switching of role play between Ohmic and Schottky barriers using different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ohmic-type contact is desired as it possesses a low resistance junction to current in both voltage polarities. [49,50] These types of contact can determine the flow of electrons from metals to semiconductors. [51] As such, the ohmic resistance of various PC ranges between 10 −4 and 10 −7 , [52] while the Schottky barrier resistance of the same type of PC ranges between 10 −3 and 10 −4 .…”
Section: Photocatalysis (Pc)mentioning
confidence: 99%
“…Ohmic-type contact is desired as it possesses a low resistance junction to current in both voltage polarities. [49,50] These types of contact can determine the flow of electrons from metals to semiconductors. [51] As such, the ohmic resistance of various PC ranges between 10 −4 and 10 −7 , [52] while the Schottky barrier resistance of the same type of PC ranges between 10 −3 and 10 −4 .…”
Section: Photocatalysis (Pc)mentioning
confidence: 99%
“…Electrochromic (EC) materials and electrochromic devices (ECDs) that show reversible color change upon application of a voltage have been widely used in a number of commercial and military applications, including energy-saving smart windows, flexible displays, , e-papers, , protective eyewear, , security, , energy storage devices, camouflage, and so on. In the past few decades, various types of materials have been established as EC materials, which can be classified into inorganic EC materials (various transition-metal oxides), organic EC materials (organic small molecules and polymers), and organic–inorganic hybrid EC materials (various metal–organic systems). Metallo-supramolecular polymers (MSPs) are generally considered as organic–inorganic hybrid EC materials because these polymers are typically synthesized by 1:1 complexation between organic ligands and metal ions. ,, Since Higuchi et al demonstrated the EC color change of MSP prepared from 1,4-bis­(2,2′:6′,2″-terpyridine-4′-yl)-benzene as a ditopic ligand and the Fe­(II) ion as the metal ion, many MSPs have been developed using bisterpyridine ligands and various metal ions like Fe 2+ , Co 2+ , Ru 2+ , Os 2+ , Cu 2+ , and so forth. , These monometallic MSPs have attracted great research attention for EC applications because of their interesting physical and optoelectronic properties like solution processability, high color contrast, fast response times, good coloration efficiency, and high durability.…”
Section: Introductionmentioning
confidence: 99%